1989
DOI: 10.1128/iai.57.7.2092-2097.1989
|View full text |Cite
|
Sign up to set email alerts
|

Effect of streptomycin administration on association of enteric pathogens with cecal tissue of mice

Abstract: The effect of streptomycin on the ability of Shigella sonnei 3SR and enterotoxigenic Escherichia coli 2SR to associate with cecal tissue of mice in vivo and in vitro was examined. After orogastric challenge, both pathogens associated in significantly greater numbers (P < 0.05) with the cecal tissue of streptomycin-treated mice than with the tissue of untreated mice. The population levels of the pathogens were also significantly greater (P < 0.05) in the cecal contents of streptomycin-treated mice than in untre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Germ free mice and Guinea pigs monocolonized with E. coli were shown to block the establishment of S. flexneri whereas monocolonization with Bacteroides, Bifidobacterium, or Streptococcus had no effect on Shigella levels (Formal et al, 1961 ; Maier and Hentges, 1972 ). Other studies have shown treatment with streptomycin produces an environment that supports Shigella colonization in mice (Pongpech et al, 1989 ; Martino et al, 2005 ). Together these studies suggest a complex interplay between Shigella and commensal bacteria that are not easily reconciled with the low infectious dose observed in humans.…”
Section: First Barriers To Shigella Infection: the Microbiota And Thementioning
confidence: 96%
“…Germ free mice and Guinea pigs monocolonized with E. coli were shown to block the establishment of S. flexneri whereas monocolonization with Bacteroides, Bifidobacterium, or Streptococcus had no effect on Shigella levels (Formal et al, 1961 ; Maier and Hentges, 1972 ). Other studies have shown treatment with streptomycin produces an environment that supports Shigella colonization in mice (Pongpech et al, 1989 ; Martino et al, 2005 ). Together these studies suggest a complex interplay between Shigella and commensal bacteria that are not easily reconciled with the low infectious dose observed in humans.…”
Section: First Barriers To Shigella Infection: the Microbiota And Thementioning
confidence: 96%
“…1C, that in the large intestines from the conventional mice fusiform bacteria are in abundance, but they are eliminated when streptomycin is administrated to the mice, as previously described(12,16). It has previously been reported that indigenous microorganisms adhere to the membrane of intestinal epithelial cells viaINFECT.…”
mentioning
confidence: 96%
“…The caecal epithelium is the primary colonisation site and port of entry for many clinically important pathogens for which mouse models exist, including Trichuris trichiura (model organism T. muris), Salmonella enterica, serovar Typhymurium, Campylobacter jejuni, Shigella sonnei, Escherichia coli (ETEC, model organism Citrobacter rodentium ), Yersinia pseudotuberculosis and Entamoeba histolytica, among others ( Lee et al, 1986 , Pongpech et al, 1989 , Houpt et al, 2002 , Barthel et al, 2003 , Klementowicz et al, 2012 , Collins et al, 2014 , Fahlgren et al, 2014 ). Developing mouse caecaloid cultures will enable host interactions of these important pathogens to be studied in an in vitro model.…”
Section: Introductionmentioning
confidence: 99%